Lightweight thermal insulation concrete and preparation method thereof
By using modified SEBS, fly ash, ceratops, composite foaming agents and modified cellulose fillers in lightweight insulation concrete, the problems of poor foam stability and insufficient crack resistance in the prior art are solved. , achieving a significant improvement in cracking resistance and thermal insulation performance.
Patent Information
- Application Number
- CN202411672443.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
During the construction process, existing lightweight insulation concrete has poor foam stability, which affects density and strength due to improper selection and proportion of foaming agents. Inadequate addition of fiber reinforced materials, resulting in insufficient crack resistance and durability.
Using modified SEBS, fly ash, ceratops, composite foaming agents and modified cellulose fillers, a flexible network is formed by modifying SEBS, fly ash is optimized internal structure, ceramic particles are reduced in density, and composite distribution is Foaming agent improves the pore structure, and modified cellulose fillers enhance integrity, and jointly improves crack resistance and thermal insulation performance.
It significantly improves the crack resistance and thermal insulation properties of concrete, ensures the stability and use performance of materials, and extends its promotion and application in a wider range of fields.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to a lightweight thermal insulation concrete and a preparation method thereof. Background Art
[0002] As an innovative building material, lightweight thermal insulation concrete has been widely used in the construction industry. This material not only has low density, but also has excellent thermal insulation performance, which can effectively reduce the energy consumption of buildings and improve living comfort. In recent years, with the popularization of green building concepts and technological advances, the application scope of lightweight thermal insulation concrete has continued to expand, and it has gradually become one of the important choices for building insulation materials. It can not only reduce the weight of the building, but also significantly improve the energy-saving effect of the building, which meets the requirements of energy conservation and environmental protection of modern buildings.
[0003] However, the existing lightweight thermal insulation concrete still has some problems in practical application. In particular, during the construction process, due to improper selection and proportion of the foaming agent, it is easy to cause poor foam stability, which in turn affects the density and strength of the concrete. In addition, improper addition of fiber reinforcement materials and improper selection of types will also lead to insufficient crack resistance and durability of the concrete. These problems not only affect the performance of lightweight thermal insulation concrete, but also limit its promotion and application in a wider range of fields. Therefore, it is urgent to develop a new type of lightweight thermal insulation concrete and its preparation method that can effectively solve the above problems. Summary of the invention
[0004] In order to improve the anti-cracking performance of concrete, the present application provides a lightweight thermal insulation concrete and a preparation method thereof.
[0005] The present application provides a lightweight thermal insulation concrete and a preparation method using the following technical solutions: In the first aspect, the present application provides a lightweight thermal insulation concrete, which adopts the following technical solution: A lightweight thermal insulation concrete comprising the following components in parts by mass: 60-100 parts of cement Modified SEBS 5-10 parts Fly ash 20-40 parts 30-60 parts of ceramsite Compound foaming agent 0.5-1.5 parts Modified cellulose filler 10-20 parts Foam stabilizer 0.005-0.015 parts Water reducing agent 0.5-1.5 parts 30-50 parts water; The raw materials for preparing the modified SEBS include SEBS bulk, itaconic acid and allyl glycidyl ether.
[0006] Modified SEBS (styrene-ethylene-butylene-styrene block copolymer) can form a flexible network in the concrete system, effectively disperse stress, prevent cracks from occurring and expanding, and thus improve anti-cracking performance. Itaconic acid and allyl glycidyl ether can give SEBS good flexibility and reactivity, change the surface properties of SEBS, and improve its compatibility with compound foaming agents. They can more stably wrap bubbles, improve the foaming effect, and make bubbles more evenly and stably distributed in concrete, thereby improving thermal insulation performance. Fly ash is filled between cement particles to optimize the internal structure, and its volcanic ash effect helps to improve the overall performance. As a lightweight aggregate, ceramsite has many internal pores, which can reduce the density of concrete and achieve lightweight. The compound foaming agent can produce a large number of uniform pores inside the concrete, which can effectively reduce heat conduction, improve thermal insulation performance, and also reduce weight. The pore structure of the modified cellulose filler itself is conducive to thermal insulation, and can interact with other materials to enhance integrity, further improve the thermal insulation effect, and synergize with the modified SEBS to improve anti-cracking performance and thermal insulation performance.
[0007] Preferably, the mass ratio of the SEBS bulk, itaconic acid and allyl glycidyl ether is 1:0.3:(0.05-0.2).
[0008] The modified SEBS prepared according to the above mass ratio has good flexibility and compatibility, can form a stable pore structure, and improve the thermal insulation performance of concrete.
[0009] Preferably, the raw materials for preparing the modified SEBS further include iron-doped nano-titanium dioxide.
[0010] As a nucleating agent, iron-doped nano-titanium dioxide can provide more nucleation sites for the foaming process, prompting the foaming agent to form a large number of uniform, small and stable bubbles at lower energy, thereby improving the foaming efficiency and quality, and forming a more dense and regular pore structure inside the concrete, effectively reducing thermal conductivity and enhancing thermal insulation performance, while further reducing the dead weight of the concrete and achieving better lightweighting; at the same time, iron-doped nano-titanium dioxide can enhance the interaction between SEBS molecular chains, making the flexible network structure formed by the modified SEBS in the concrete more stable, effectively improving the concrete's anti-cracking performance, and optimizing the overall performance of lightweight thermal insulation concrete.
[0011] Preferably, the composite foaming agent includes azodicarbonamide, zinc oxide and dicumyl peroxide.
[0012] Azodicarbonamide will decompose under heat conditions to produce a large amount of nitrogen. These nitrogen gases form bubbles, which promote the foaming of concrete, effectively reduce the density of concrete, achieve lightweight and increase porosity, thereby improving thermal insulation performance; zinc oxide, as an activator, can reduce the decomposition temperature of azodicarbonamide, speed up the decomposition rate, make the foaming process more efficient, and help form evenly distributed bubbles inside the concrete; diisopropylbenzene peroxide can adjust the progress of the foaming reaction, optimize the size and distribution of bubbles, prevent excessive merging of bubbles, make the foam structure more stable and uniform, further enhance the thermal insulation and lightweight properties of concrete, and at the same time ensure the quality stability of concrete during the foaming process; the three work synergistically to improve the foaming effect of concrete.
[0013] Preferably, the mass ratio of azodicarbonamide, zinc oxide and dicumyl peroxide is 1:0.05:(0.01-0.02).
[0014] The foaming agent compounded according to the above mass ratio has good foaming performance, can improve the uniformity and stability of the concrete pore structure, thereby effectively improving its thermal insulation performance.
[0015] Preferably, the azodicarbonamide is subjected to modification treatment to obtain modified azodicarbonamide, and the raw materials for preparing the modified azodicarbonamide include azodicarbonamide body and ethylene oxide.
[0016] The introduction of ethylene oxide can increase the hydrophilicity of azodicarbonamide, improve its uniformity in the foaming system, and help produce finer and more stable bubbles; the modified azodicarbonamide is more compatible with other foaming agent components and other materials in concrete, and can work better together to further enhance the thermal insulation performance and lightweight effect of lightweight thermal insulation concrete, while also helping to improve the overall stability of the concrete.
[0017] Preferably, the raw materials for preparing the modified cellulose filler include pretreated bamboo fiber, phthalic anhydride and cinnamoyl chloride.
[0018] Pretreated bamboo fiber has a good pore structure, which plays a filling and reinforcing role in concrete, helping to improve the integrity of concrete; phthalic anhydride can introduce ester groups on the surface of bamboo fiber, improving the compatibility of bamboo fiber, thereby making the internal structure of concrete more stable and improving anti-cracking performance; cinnamoyl chloride improves the dispersibility of bamboo fiber in concrete, allowing bamboo fiber to be more evenly distributed in concrete, which can effectively reduce the heat conduction of concrete and enhance thermal insulation performance; the addition of bamboo fiber is also conducive to reducing the dead weight of concrete, achieving lightweight, and improving the comprehensive performance of lightweight thermal insulation concrete.
[0019] Preferably, the pretreated bamboo fiber is prepared by the following steps: The bamboo is cut, defoliated, and sliced, and then soaked in water and then steamed with a sodium hydroxide aqueous solution to obtain treated bamboo. The treated bamboo is then rinsed with water, dried, and crushed to obtain pretreated bamboo fiber.
[0020] The pretreated bamboo fiber prepared according to the above steps has a good pore structure and can form an interwoven network structure in the concrete, thereby improving the stability of the concrete, reducing heat conduction, and improving its thermal insulation performance.
[0021] Preferably, the mass ratio of the pretreated bamboo fiber, phthalic anhydride and cinnamoyl chloride is 1:0.2:(0.05-0.15).
[0022] The modified cellulose filler prepared according to the above mass ratio can effectively improve the stability of concrete and enhance its thermal insulation performance and anti-cracking performance.
[0023] In a second aspect, the present application provides a method for preparing lightweight thermal insulation concrete, which adopts the following technical solution: A method for preparing lightweight thermal insulation concrete comprises the following steps: The cement, modified SEBS, fly ash and modified cellulose filler are mixed and stirred, ceramsite is added, and stirred to obtain a dry mix; a water reducer is added into water, and stirred evenly to obtain a water reducer solution; a compound foaming agent and a foam stabilizer are dispersed into water to obtain a foaming agent dispersion; water is added into the dry mix, stirred, and then the water reducer solution is added, and stirred to obtain a wet mix; the foaming agent dispersion is added into the wet mix, and pressure foaming is performed to obtain a lightweight thermal insulation concrete.
[0024] The lightweight thermal insulation concrete prepared according to the above steps has a uniform and fine pore structure and has good thermal insulation performance and anti-cracking performance.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Modified SEBS can form a flexible network in the concrete system, effectively disperse stress, prevent cracks from occurring and expanding, and thus improve anti-cracking performance. Itaconic acid and allyl glycidyl ether can give SEBS good flexibility and reactivity, change the surface properties of SEBS, and improve its compatibility with the foaming agent. They can more stably wrap bubbles, improve the foaming effect, and make the bubbles more evenly and stably distributed in the concrete, thereby improving the thermal insulation performance. Fly ash is filled between cement particles to optimize the internal structure, and its volcanic ash effect helps to improve the overall performance. As a lightweight aggregate, ceramsite has many internal pores, which can reduce the density of concrete and achieve lightweight. The compound foaming agent can produce a large number of uniform pores inside the concrete, which can effectively reduce heat conduction, improve thermal insulation performance, and also reduce weight. The pore structure of the modified cellulose filler itself is conducive to thermal insulation, and can interact with other materials to enhance integrity, further improve the thermal insulation effect, and synergize with the modified SEBS to improve anti-cracking performance and thermal insulation performance.
[0026] 2. Azodicarbonamide will decompose under heating conditions to produce a large amount of nitrogen. These nitrogen gases form bubbles, which promote the foaming of concrete, effectively reduce the density of concrete, achieve lightweight and increase porosity, thereby improving thermal insulation performance; zinc oxide, as an activator, can reduce the decomposition temperature of azodicarbonamide, accelerate the decomposition rate, make the foaming process more efficient, and help form evenly distributed bubbles inside the concrete; diisopropylbenzene peroxide can adjust the progress of the foaming reaction, optimize the size and distribution of bubbles, prevent excessive merging of bubbles, make the foam structure more stable and uniform, further enhance the thermal insulation and lightweight properties of concrete, and at the same time ensure the quality stability of concrete during the foaming process; the three work synergistically to improve the foaming effect of concrete.
[0027] 3. Pretreated bamboo fiber has a good pore structure, which plays a filling and reinforcing role in concrete, helping to improve the integrity of concrete; phthalic anhydride can introduce ester groups on the surface of bamboo fiber, improving the compatibility of bamboo fiber, thereby making the internal structure of concrete more stable and improving anti-cracking performance; cinnamoyl chloride improves the dispersibility of bamboo fiber in concrete, allowing bamboo fiber to be more evenly distributed in concrete, which can effectively reduce the heat conduction of concrete and enhance thermal insulation performance; the addition of bamboo fiber is also conducive to reducing the dead weight of concrete, achieving lightweight, and improving the comprehensive performance of lightweight thermal insulation concrete. DETAILED DESCRIPTION
[0028] The present application discloses a lightweight thermal insulation concrete and a preparation method. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw materials description: SEBS (CAS No.: 66070-58-4), molecular weight 100,000, benzoyl peroxide (CAS No.: 94-36-0), itaconic acid (CAS No.: 97-65-4), allyl glycidyl ether (CAS No.: 106-92-3), iron-doped nano-titanium dioxide model JR05N, purchased from Hangzhou Zheming New Materials Co., Ltd., azodicarbonamide (CAS No.: 123-77-3), ethylene oxide (CAS No.: 75-21-8), bamboo is moso bamboo, phthalic anhydride (CAS No. :85-44-9), cinnamoyl chloride (CAS No.: 102-92-1), cement is silicate cement PO42.5, fly ash is Class II fly ash, fineness is 15%, water requirement ratio is 95%, loss on ignition is 2%, ceramsite is building ceramsite, specification is 5-15mm, purchased from Hangzhou Cancai Building Materials Technology Co., Ltd., water reducer model is TC-PCA-ZQJ, purchased from Xi'an Tongcheng Building Technology Co., Ltd., diisopropylbenzene peroxide (CAS No.: 80-43-3), and polypropylene fiber is purchased from Changzhou Tianyi Engineering Fiber Co., Ltd.
[0029] Preparation Example 1 Preparation of modified SEBS 14.82 kg of SEBS was added to 50 L of toluene, and stirred at 80°C at 300 rpm under a nitrogen atmosphere until it was uniformly dissolved to obtain a SEBS solution; 0.075 kg of benzoyl peroxide was added to the SEBS solution, and the mixture was stirred at 300 rpm for 20 min, then the temperature was raised to 120°C, 4.44 kg of itaconic acid and 0.74 kg of allyl glycidyl ether were added within 1 h, and after the addition was completed, the mixture was kept at 120°C for 6 h, and after cooling to 30°C, anhydrous ethanol was added for precipitation, the precipitate was collected by filtration, the precipitate was washed with anhydrous ethanol, and then dried in an oven at 60°C to constant weight to obtain a product, which was added to a twin-screw extruder and extruded and granulated at 180°C to obtain a modified SEBS.
[0030] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that in Preparation Example 2, the amount of SEBS used is 13.33 kg, the amount of itaconic acid used is 4 kg, and the amount of allyl glycidyl ether used is 2.67 kg.
[0031] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the amount of SEBS used is 14.04 kg, the amount of itaconic acid used is 4.21 kg, and the amount of allyl glycidyl ether used is 1.75 kg.
[0032] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. The only difference between Preparation Example 4 and Preparation Example 1 is that allyl glycidyl ether is not added in Preparation Example 4, the amount of SEBS used is 15.38 kg, and the amount of itaconic acid used is 4.62 kg.
[0033] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the amount of SEBS used is 12.9 kg, the amount of itaconic acid used is 3.87 kg, and the amount of allyl glycidyl ether used is 3.23 kg.
[0034] Preparation Example 6 Preparation Example 6 is based on Preparation Example 1. The only difference between Preparation Example 6 and Preparation Example 1 is that the modified SEBS in Preparation Example 6 also includes iron-doped nano-titanium dioxide.
[0035] 14.82 kg of SEBS was added to 50 L of toluene, and stirred at 80° C. and 300 rpm under a nitrogen atmosphere until it was uniformly dissolved to obtain a SEBS solution; 0.075 kg of benzoyl peroxide was added to the SEBS solution, and the mixture was stirred at 300 rpm for 20 min, and then the temperature was raised to 120° C., and 4.44 kg of itaconic acid and 0.74 kg of allyl glycidyl ether were added within 1 h. After the addition was completed, the mixture was kept at 120° C. for 6 h, and after cooling to 30° C., anhydrous ethanol was added for precipitation, and the precipitate was collected by filtration. After washing the precipitate with anhydrous ethanol, the precipitate was dried in an oven at 60° C. to constant weight to obtain a product, and the product and 2% of the mass of the product of iron-doped nano-titanium dioxide were added to a twin-screw extruder, mixed and kneaded at 180° C., and then extruded and granulated to obtain a modified SEBS.
[0036] Preparation Example 7 Preparation of modified azodicarbonamide Under a nitrogen atmosphere, 5 kg of azodicarbonamide was dispersed in 20 L of N, N-dimethylformamide, and stirred at a speed of 200 rpm until fully dissolved to obtain an azodicarbonamide solution; 0.05 kg of potassium hydroxide and 1.5 kg of ethylene oxide were added to the azodicarbonamide solution, and the ethylene oxide was added within 2 hours. The reaction was stirred at a speed of 200 rpm at 50°C for 4 hours, and after cooling to 30°C, deionized water was added for precipitation, and the precipitate was obtained by filtration. The precipitate was washed with deionized water, and vacuum dried at 80°C to constant weight to obtain modified azodicarbonamide.
[0037] Preparation Example 8 Preparation of pretreated bamboo fiber The bamboo was cut, de-greened, and sliced, and then soaked in water for 1 day, and then steamed with a sodium hydroxide aqueous solution, the mass ratio of bamboo, water and sodium hydroxide was 1:10:0.2, and treated at 120°C for 3 hours to obtain the treated bamboo. The treated bamboo was rinsed with water, dried at 80°C for 4 hours, and crushed to a fineness of 300 meshes to obtain pretreated bamboo fiber.
[0038] Preparation Example 9 Preparation of modified cellulose filler 24 kg of pretreated bamboo fiber prepared in Preparation Example 8, 4.8 kg of phthalic anhydride and 1.2 kg of cinnamoyl chloride were dispersed in 50 L of N,N-dimethylformamide, and heated to 120 ° C with a stirring speed of 300 rpm under nitrogen protection for 6 hours. After cooling to 30 ° C, it was filtered, washed with deionized water 3 times, and dried at 80 ° C to constant weight to obtain a modified cellulose filler.
[0039] Preparation Example 10 Preparation Example 10 is based on Preparation Example 9. The only difference between Preparation Example 10 and Preparation Example 9 is that in Preparation Example 10, the amount of pretreated bamboo fiber used is 22.23 kg, the amount of phthalic anhydride used is 4.44 kg, and the amount of cinnamoyl chloride used is 3.33 kg.
[0040] Preparation Example 11 Preparation Example 11 is based on Preparation Example 9. The only difference between Preparation Example 11 and Preparation Example 9 is that in Preparation Example 11, the amount of pretreated bamboo fiber used is 23.08 kg, the amount of phthalic anhydride used is 4.62 kg, and the amount of cinnamoyl chloride used is 2.3 kg.
[0041] Preparation Example 12 Preparation Example 12 is based on Preparation Example 9. The only difference between Preparation Example 12 and Preparation Example 9 is that cinnamoyl chloride is not added in Preparation Example 12, the amount of pretreated bamboo fiber is 25 kg, and the amount of phthalic anhydride is 5 kg.
[0042] Preparation Example 13 Preparation Example 13 is based on Preparation Example 9. The only difference between Preparation Example 13 and Preparation Example 9 is that in Preparation Example 13, the amount of pretreated bamboo fiber used is 21.42 kg, the amount of phthalic anhydride used is 4.29 kg, and the amount of cinnamoyl chloride used is 4.29 kg.
[0043] Example 1 60kg of cement, 5kg of modified SEBS prepared in Preparation Example 1, 20kg of fly ash, and 10kg of modified cellulose filler prepared in Preparation Example 9 were stirred at a speed of 100rpm for 3min, and 30kg of ceramsite was added and stirred at a speed of 150rpm for 5min to obtain a dry mix; 0.5kg of water reducer was added to 1.5kg of water and stirred evenly at a speed of 200rpm to obtain a water reducer solution; 0.5kg of compound foaming agent and 0.005kg of foam stabilizer were dispersed in 3kg of water to obtain a foaming agent dispersion, in which the mass ratio of azodicarbonamide, zinc oxide and diisopropylbenzene peroxide in the compound foaming agent was 1:0.05:0.01; the total amount of water was 30kg, the remaining water was added to the dry mix, stirred at a speed of 200rpm for 5min, the water reducer solution was added, and stirred at a speed of 200rpm for 8min to obtain a wet mix; the foaming agent dispersion was added to the wet mix for pressure foaming to obtain a lightweight thermal insulation concrete.
[0044] Example 2 100kg of cement, 10kg of modified SEBS prepared in Preparation Example 2, 40kg of fly ash, and 20kg of modified cellulose filler prepared in Preparation Example 10 were stirred at a speed of 100rpm for 3min, 60kg of ceramsite was added, and stirred at a speed of 150rpm for 5min to obtain a dry mix; 1.5kg of water reducer was added to 5kg of water, and stirred evenly at a speed of 200rpm to obtain a water reducer solution; 1.5kg of compound foaming agent and 0.015kg of foam stabilizer were dispersed in 10kg of water to obtain a foaming agent dispersion, in which the mass ratio of azodicarbonamide, zinc oxide and diisopropylbenzene peroxide in the compound foaming agent was 1:0.05:0.02; the total amount of water was 50kg, the remaining water was added to the dry mix, stirred at a speed of 200rpm for 5min, the water reducer solution was added, and stirred at a speed of 200rpm for 8min to obtain a wet mix; the foaming agent dispersion was added to the wet mix, pressure foaming was performed, and lightweight thermal insulation concrete was obtained.
[0045] Example 3 80kg of cement, 7.5kg of modified SEBS prepared in Preparation Example 3, 30kg of fly ash, and 15kg of modified cellulose filler prepared in Preparation Example 11 were stirred at a speed of 100rpm for 3min, and 45kg of ceramsite was added and stirred at a speed of 150rpm for 5min to obtain a dry mix; 1kg of water reducer was added to 3kg of water and stirred evenly at a speed of 200rpm to obtain a water reducer solution; 1kg of compound foaming agent and 0.01kg of foam stabilizer were dispersed in 6kg of water to obtain a foaming agent dispersion, in which the mass ratio of azodicarbonamide, zinc oxide and diisopropylbenzene peroxide in the compound foaming agent was 1:0.05:0.015; the total amount of water was 40kg, the remaining water was added to the dry mix, stirred at a speed of 200rpm for 5min, the water reducer solution was added, and stirred at a speed of 200rpm for 8min to obtain a wet mix; the foaming agent dispersion was added to the wet mix for pressure foaming to obtain a lightweight thermal insulation concrete.
[0046] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the modified SEBS prepared in Preparation Example 3 is replaced by the modified SEBS prepared in Preparation Example 4.
[0047] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the modified SEBS prepared in Preparation Example 3 is replaced by the modified SEBS prepared in Preparation Example 5.
[0048] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the modified SEBS prepared in Preparation Example 3 is replaced by the modified SEBS prepared in Preparation Example 6.
[0049] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, azodicarbonamide is replaced by Preparation Example 7 to prepare modified azodicarbonamide.
[0050] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that the mass ratio of azodicarbonamide, zinc oxide and diisopropylbenzene peroxide in the composite foaming agent in Example 8 is 1:0.05:0.005.
[0051] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that the mass ratio of azodicarbonamide, zinc oxide and diisopropylbenzene peroxide in the composite foaming agent in Example 9 is 1:0.05:0.025.
[0052] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the modified cellulose filler prepared in Preparation Example 11 is replaced by the modified cellulose filler prepared in Preparation Example 12.
[0053] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, the modified cellulose filler prepared in Preparation Example 11 is replaced by the modified cellulose filler prepared in Preparation Example 13.
[0054] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, modified SEBS is replaced by SEBS.
[0055] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the modified cellulose filler is replaced by polypropylene fiber.
[0056] Performance testing (1) Select "GB / T13475-2008 Determination and calibration of adiabatic steady-state heat transfer properties and guarded hot box method" as the standard to measure the thermal conductivity of the sample. Each sample is tested three times and the average value is taken after measurement. The results are recorded in Table 1.
[0057] (2) Select GB / T 50082-2024 Standard for Test Methods for Long-term Performance and Durability of Concrete as the standard, conduct early crack resistance test on the samples, and record the total crack area per unit area (mm 2 / m 2 ). Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0058] Table 1 Test results of thermal insulation performance and crack resistance of lightweight thermal insulation concrete Test results Thermal conductivity (W / (m·k)) <![CDATA[Total cracking area (mm 2 / m 2 )]]> Example 1 0.34 25.33 Example 2 0.32 24.79 Example 3 0.31 24.65 Example 4 0.43 30.19 Example 5 0.38 35.74 Example 6 0.25 21.23 Example 7 0.23 22.69 Example 8 0.56 36.85 Example 9 0.62 39.21 Example 10 0.56 42.5 Embodiment 11 0.49 38.3 Comparative Example 1 0.72 45.7 Comparative Example 2 0.65 53.8 It can be seen from Table 1 that the thermal conductivity of Examples 1-3 is less than 0.31 W / (m·k), and the total crack area is less than 25.33 mm 2 / m 2 It can be seen that the lightweight thermal insulation concrete prepared in this application has good thermal insulation performance and anti-cracking performance.
[0059] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that the composition and proportion of the synthetic components in the modified SEBS are changed in Examples 4 and 5. Compared with Example 3, the thermal insulation performance and anti-cracking performance of Examples 4 and 5 are reduced. This is because the limited ratio is destroyed, the stability of the modified SEBS is reduced, the flexibility and compatibility are reduced, the foaming performance is deteriorated, the internal structure of the concrete is affected, and the thermal insulation performance and anti-cracking performance are deteriorated.
[0060] As can be seen from Table 1, the only difference between Example 6 and Example 3 is that iron-doped nano-titanium dioxide is further added to the modified SEBS in Example 6. Compared with Example 3, the thermal insulation performance and anti-cracking performance of Example 6 are improved; this is because iron-doped nano-titanium dioxide can improve the foaming performance of the modified SEBS and the stability of the internal structure of the concrete, thereby improving the thermal insulation performance and anti-cracking performance.
[0061] As can be seen from Table 1, the only difference between Example 7 and Example 3 is that in Example 7, azodicarbonamide is replaced by modified azodicarbonamide prepared in Preparation Example 7. Compared with Example 3, the thermal insulation performance and anti-cracking performance of Example 7 are improved; this is because the modification treatment with propylene oxide enhances the hydrophilicity and compatibility of azodicarbonamide, which helps to produce more dense and stable bubbles, thereby improving the thermal insulation performance and anti-cracking performance of concrete.
[0062] As can be seen from Table 1, the only difference between Examples 8 and 9 and Example 3 is that the mass ratio of azodicarbonamide, zinc oxide and dicumyl peroxide in the composite foaming agent in Example 8 is 1:0.05:0.005, and the mass ratio of azodicarbonamide, zinc oxide and dicumyl peroxide in the composite foaming agent in Example 9 is 1:0.05:0.025. Compared with Example 3, the thermal insulation performance and crack resistance of Examples 8 and 9 are reduced; this is because the limited ratio of the composite foaming agent is destroyed, which affects the stability and uniformity of the internal bubbles, and then affects the stability of the concrete, so that the thermal insulation performance and crack resistance are reduced.
[0063] As can be seen from Table 1, the only difference between Examples 10 and 11 and Example 3 is that the component composition and ratio of the modified cellulose filler in Examples 10 and 11 are changed, and the thermal insulation performance and anti-cracking performance of Examples 10 and 11 are reduced compared with Example 3; this is because too much or too little cinnamoyl chloride will affect the dispersibility of bamboo fiber, thereby affecting its performance, and the stability of the internal structure of concrete is reduced, thereby reducing the thermal insulation performance and anti-cracking performance.
[0064] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that the modified SEBS is replaced by SEBS in Comparative Example 1, and the thermal insulation performance and anti-cracking performance of Comparative Example 1 are significantly reduced compared with Example 3; this is because the modified SEBS is replaced by SEBS, lacks modification treatment, and the compatibility and flexibility of SEBS are reduced; the foaming effect is deteriorated, the stability of the system is reduced, and then the thermal insulation performance and anti-cracking performance are significantly reduced.
[0065] As can be seen from Table 1, the only difference between Comparative Example 2 and Example 3 is that the modified cellulose filler is replaced with polypropylene fiber in Comparative Example 2. Compared with Example 3, the thermal insulation performance and anti-cracking performance of Comparative Example 2 are significantly reduced; this is because the polypropylene fiber lacks a good pore structure and compatibility, the stability of the concrete system is reduced, and the thermal insulation performance and anti-cracking performance are significantly reduced.
[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A lightweight thermal insulation concrete, characterized in that: The composition includes the following components in parts by weight: 60-100 parts of cement Modified SEBS 5-10 parts Fly ash 20-40 parts 30-60 parts of ceramsite Compound foaming agent 0.5-1.5 parts Modified cellulose filler 10-20 parts Foam stabilizer 0.005-0.015 parts Water reducing agent 0.5-1.5 parts 30-50 parts water; The raw materials for preparing the modified SEBS include SEBS bulk, itaconic acid and allyl glycidyl ether.
2. The lightweight thermal insulation concrete according to claim 1, characterized in that: The mass ratio of the SEBS body, itaconic acid and allyl glycidyl ether is 1:0.3:(0.05-0.2).
3. A lightweight thermal insulation concrete according to claim 2, characterized in that: The raw materials for preparing the modified SEBS also include iron-doped nano titanium dioxide.
4. The lightweight thermal insulation concrete according to claim 1, characterized in that: The composite foaming agent comprises azodicarbonamide, zinc oxide and dicumyl peroxide.
5. A lightweight thermal insulation concrete according to claim 4, characterized in that: The mass ratio of the azodicarbonamide, zinc oxide and dicumyl peroxide is 1:0.05:(0.01-0.02).
6. The lightweight thermal insulation concrete according to claim 5, characterized in that: The azodicarbonamide is subjected to modification treatment to obtain modified azodicarbonamide, and the raw materials for preparing the modified azodicarbonamide include azodicarbonamide body and ethylene oxide.
7. The lightweight thermal insulation concrete according to claim 1, characterized in that: The raw materials for preparing the modified cellulose filler include pretreated bamboo fiber, phthalic anhydride and cinnamoyl chloride.
8. The lightweight thermal insulation concrete according to claim 7, characterized in that: The pretreated bamboo fiber is prepared by the following steps: The bamboo is cut, defoliated, and sliced, and then soaked in water and then steamed with a sodium hydroxide aqueous solution to obtain treated bamboo. The treated bamboo is then rinsed with water, dried, and crushed to obtain pretreated bamboo fiber.
9. The lightweight thermal insulation concrete according to claim 8, characterized in that: The mass ratio of the pretreated bamboo fiber, phthalic anhydride and cinnamoyl chloride is 1:0.2:(0.05-0.15).
10. A method for preparing the lightweight thermal insulation concrete as claimed in claims 1 to 9, characterized in that: The steps include: The cement, modified SEBS, fly ash and modified cellulose filler are mixed and stirred, ceramsite is added, and stirred to obtain a dry mix; a water reducer is added into water, and stirred evenly to obtain a water reducer solution; a compound foaming agent and a foam stabilizer are dispersed into water to obtain a foaming agent dispersion; water is added into the dry mix, stirred, and then the water reducer solution is added, and stirred to obtain a wet mix; the foaming agent dispersion is added into the wet mix, and pressure foaming is performed to obtain a lightweight thermal insulation concrete.